Teachers’ Perspectives on the Education of Deaf and Hearing Difficulty Students in Indonesia: Research at SLB-B Negeri Cicendo Bandung - Rosida Marasabessy (Indonesian Journal of Community and Special Needs Education, 2023)
Deaf and hard-of-hearing students are a group of people who need special education, but that has not been fulfilled in the Indonesian education system. This research is field research conducted at SLB-B Negeri Cicendo Bandung, the oldest deaf school in Indonesia, located in Bandung. This research was conducted by observing the activities of students in the classroom and in-depth interviews with their teachers; this was done to initiate discussions about various aspects of their education. Problems with language and speech mastery, teaching methods, students' dialectical relationships with technology, and experiences of stigma are used to bring out their life experiences. The study underscores the need to develop and improve the ability to master spoken and spoken language and academic content development. This will increase the access of deaf students to a wide range of disciplines and allow them to go beyond the basic level of attainment.